Settlement of Customary Law Community Land Disputes in Byosi Village Keerom Regency Perspective of Regulation of the Minister of State for Agrarian Affairs/KBPN Number 5 of 1999 - James Yoseph Palenewen (Dinasti Research, 2024)
Customary land disputes occur in customary law communities in Byosi village, Keerom Regency, where customary land ownership often overlaps in the same location or place and can be owned by two or more people. This is what causes problems and there are disputes over customary land between customary law communities. The aim of this research is to determine the resolution of disputes over overlapping customary land ownership among customary law communities in Byosi Village, Keerom Regency. This research method is normative juridical and empirical, a research method that refers to legal norms contained in statutory regulations, library materials, written regulations or other legal materials that are secondary in nature and also realities that occur in the midst of Byosi traditional law community, Keerom Regency. The results of this research reveal that the resolution of disputes over overlapping customary land ownership in Byosi Village was carried out using deliberation which was chosen because it suited the character and way of life of the traditional law community in Byosi Village which was familial in nature, compared to resolving disputes through court institutions which tended to be confrontational in nature. , takes more into account winning and losing, takes into account more realistic aspects and ignores the social elements in traditional communities which are familial in nature.